Effect of voltage gradient on ohmic thawing characteristics of sour cherry juice concentrates for the temperature range of −18℃ to +4℃. (December 2019) - Cokgezme, Omer Faruk; Icier, Filiz
Frozen sour cherry juice concentrates having 15%, 30%, 40% and 50% total soluble solid (TSS) contents were thawed by ohmic thawing (OT; 10 V/cm, 15 V/cm and 20 V/cm) and conventional thawing (CT; at 4 ℃). To enhance the electrode-sample contact during OT, the thawing cell was custom-designed. Thawing times were shortened about 90% by OT. Thermal images were taken to determine temperature homogeneity. As OT proceeded, a small amount of frozen sample having a relatively lower density raised up to the surface of the sample. It resulted in temperature heterogeneity in the surface due to relatively rapid temperature increment in thawed regions during OT. The change of effective electrical conductivity (EEC) in the temperature range of −18 ℃ and 4 ℃ was determined and it varied between 0.005 and 0.25 s/m. For the same temperature, EEC increased as TSS increased up to 40% (p<0.05). EEC–temperature relations were characterized by a polynomial model.